2017
DOI: 10.1063/1.4999626
|View full text |Cite
|
Sign up to set email alerts
|

Obtainment of the density of states in the band tails of hydrogenated amorphous silicon

Abstract: In this work, we present two new pairs of formulas to obtain a spectroscopy of the density of states (DOS) in each band tail of hydrogenated amorphous silicon (a-Si:H) from photoconductivity-based measurements. The formulas are based on the knowledge of the small-signal recombination lifetime s 0 , the characteristic decay time of the concentration of trapped carriers generated in excess by the illumination, and that can be measured by methods like the Oscillating Photocarrier Grating (OPG) or Moving Grating T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…When MGT is combined with other photoconductivity-based techniques, it can also be used for the estimation of the DOS. 9,11 Ventosinos et al 8 suggested that MGT is equivalent to the Oscillating Photocarrier Grating technique (OPG), i.e., the MGT current could be obtained by using another experimental configuration that produces a slightly different illumination. OPG also uses an interference pattern superimposed on a uniform background illumination of much higher intensity, although its movement is periodic: it moves at constant velocity for half a period, whereas in the next semiperiod it moves at the same speed but in the opposite direction.…”
Section: Articlementioning
confidence: 99%
“…When MGT is combined with other photoconductivity-based techniques, it can also be used for the estimation of the DOS. 9,11 Ventosinos et al 8 suggested that MGT is equivalent to the Oscillating Photocarrier Grating technique (OPG), i.e., the MGT current could be obtained by using another experimental configuration that produces a slightly different illumination. OPG also uses an interference pattern superimposed on a uniform background illumination of much higher intensity, although its movement is periodic: it moves at constant velocity for half a period, whereas in the next semiperiod it moves at the same speed but in the opposite direction.…”
Section: Articlementioning
confidence: 99%
“…For that purpose, using typical material parameters for undoped a-Si:H (listed in the first two columns of table 1), the fundamental equations of section 2 and appendix A are solved without approximations. By solving the charge neutrality equation for a certain temperature under dark conditions we find the Fermi level, and with this value we obtain the thermal equilibrium free carrier concentrations, n e and p e [27]. For the same temperature and different generation rates, we calculate the steady-state free carrier concentrations n and p by solving simultaneously the continuity and charge neutrality equations.…”
Section: Basics Of the Methodsmentioning
confidence: 99%
“…Above room temperature, the overestimation does not reach 41%, but at the lowest temperature, it exceeds 200%. Some papers [6,16,29,30] make the approximation γ n + γ p ∼ 2 in order to determine the minority carrier diffusion length from the ambipolar diffusion length, L 2 p = L 2 amb / (γ n + γ p ) ≃ L 2 amb /2, which is an extra but generally a lower source of errors [11].…”
Section: Parametermentioning
confidence: 99%
“…This one was the procedure used for extracting the points presented in figure 14. A simpler and more popular version of this approach is obtained by approximating γ n + γ p by 2 in the previous formula to obtain L 2 p directly from L 2 D [6,11,16,29,30]. With this extra approximation, the L 2 p values are sometimes higher than those obtained from the multi-voltage approach.…”
Section: Estimation Of Lmentioning
confidence: 99%